Limited spread of pathology within the brainstem of α-synuclein BAC transgenic mice inoculated with preformed fibrils into the gastrointestinal tract. (18th January 2020) - Uemura, Norihito; Yagi, Hisashi; Uemura, Maiko T.; Yamakado, Hodaka; Takahashi, Ryosuke
Highlights: BAC transgenic mice had 1.5-/6-fold more α-Syn in the brains/stomach, respectively. BAC transgenic mice were inoculated with α-Syn PFFs into the gastric wall. Transgenic α-Syn expression promoted induction of α-Syn pathology in the brainstem. Phosphorylated α-Syn–positive neurons in the brainstem decreased in number over time. Transgenic α-Syn expression did not facilitate subsequent caudo-rostral spread. Abstract: Parkinson's disease (PD) is pathologically characterized by intraneuronal α-synuclein (α-Syn) aggregates called Lewy bodies (LBs) as well as the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). On the basis of autopsy studies, Braak et al. hypothesized that Lewy pathology initially occurs in the enteric nervous system, subsequently spreading to the dorsal motor nucleus of the vagus nerve (dmX) and then ascending in the brainstem to the SNpc. However, this hypothetical progression lacks adequate experimental evidence. We previously reported that inoculation of α-Syn preformed fibrils (PFFs) into the gastric wall of wild-type (WT) mice induced LB-like α-Syn aggregates in the dmX via the vagus nerve. However, α-Syn pathology did not spread beyond the dmX up to 12 months postinoculation. In the present study, we inoculated α-Syn PFFs into the gastric wall of bacterial artificial chromosome (BAC) transgenic mice harboring the human α-Syn gene with an A53 T mutation and analyzed the pathology. The transgenic mice had ∼1.5-fold overexpression of α-Syn in the brains and ∼6-fold overexpression of α-Syn in the stomach compared with WT mice. After inoculation of α-Syn PFFs, the transgenic mice developed a higher number of phosphorylated α-Syn (p-α-Syn)–positive neurons in the dmX compared with similarly inoculated WT mice. However, the number of p-α-Syn–positive neurons in the dmX decreased over time, and α-Syn pathology was not observed in other brain regions except in the ambiguous nucleus up to 8 months postinoculation. Taken together, BAC transgenic expression of α-Syn facilitated induction of α-Syn pathology in the brainstem, but not subsequent caudo-rostral spread in accordance with Braak's hypothesis.